Prevalência e fatores associados à queda de idosos atendidos por um serviço de atenção domiciliar privado - Juliana Peixoto Albuquerque (2014)
This study aims establishing the prevalence of falls within a group of elderly covered by a private home care service and its associated factors. A cross-section research has been conducted with a sample of 202 elderly serviced by a privet home care institution (Case Management) located in the city of Juiz de Fora, state of Minas Gerais. The data was collected through personal interview inserted into a survey, which included social-demographic, clinical and behavioral information about the elderly. Alongside the interview were conducted evaluation tests assessing cognitive level, dependency level for fulfillment of basic daily life activities, balance and mobility, fearfulness towards falling and home environment. There were performed descriptive as well as bivariate and logistic regression analysis. The average age was 85 years old, being 76% of the interviewed, women, 87% white Caucasian and 60% widows. Among the 202 elderly, 15% live alone; 69,3% wear glasses; 33,22% make use of some sort of walking support device and 67,8% are polymedicated. Results related to pre-existing pathologies show that 66,8% of the sample have systemic arterial hypertension and 24,2% suffer from diabetes mellitus. It's evident that 37,2% of the interviewed patients present total or severe dependency levels for fulfilling basic daily life activities and 52% have shown some alteration in the cognitive test. The verified prevalence of falls was of 55% (111/202), aggravated by the fact that 22,5% of the elderly affirm to have fallen more than once in the past year. 24% of all falls have resulted in fractures. The following variables accounted for the final model and better explain the occurrence of falls: the use of glasses, lack of immediate balance upon standing up, instability of the torso, the attempt of reaching things above the head or picking up from the ground. It can be noticed that the profile of the sample is highly heterogeneous in relation to the social-demographic as well as the behavioral and clinical characteristics encountered among the regular elderly population in Brazil. Nonetheless, the sample also resembles the characteristics found in other populations assisted by home care services. Given the results obtained from the study it's possible to affirm that falling is an extremely common event, consequent of physical and psychological factors, which corroborates to the fact that fall prevention for the elderly should be multi-sector, multi-professional and multi-factorial.